Hubungan antara Motivasi Kerja dengan Organizational Citizenship Behavior (OCB) pada Karyawan - Dina Mariani; Findy Suri N*; Ayudia Popy Sesilia (Universitas Syiah Kuala, 2023)
This study aims to look at the correlation between work motivation and organizational citizenship behavior (OCB) among PT. Bridgestone Sumatra Rubber Estate Dolok Merangir. The sample in this study were HRD employees, totaling 45 people. The sampling technique used is the total sampling technique. Data collection was carried out using a Likert scale model. The results of the study using the correlation technique r Product Moment ) are known to be 0.648 with p = 0.000 0.05. This means that there is a significant positive relationship between work motivation and organizational citizenship behavior (OCB) in employees. Based on the results of data analysis, it is known that employee motivation is high with a hypothetical mean (65) empirical mean (78.15) and the difference exceeds one SD (9.532), organizational citizenship behavior (OCB) is high with a hypothetical mean (75) the empirical mean (90.13) and the difference exceeds one SD (13.649). Work motivation has a contribution to organizational citizenship behavior (OCB) of 41.9%.